Proceedings of the 2017 3rd International Conference on Humanities and Social Science Research (ICHSSR 2017) 2017
DOI: 10.2991/ichssr-17.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Support on Subjective Well-being:Mediator Roles of Self-esteem and Self-efficacy

Abstract: Abstract. Numerous studies have illustrated the relationship between social support and subjective well-being, the intermediary between this has not been examined detailedly. The article aims to explore the college students' subjective well-being on the background of cultural integration and social development, as well as the relationship between social support and subjective well-being: mediator roles of self-esteem and self-efficacy. The results indicated that: (1) Social support has positive effect on subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…This is in line with the result of the study stating that social support and acceptance significantly affect student's subjective well-being (Tian et al, 2015). A study found that social support positively affects Chinese college students' subjective well-being (Xi, Wang, & Jia, 2017). The result of the study conducted on older adults and old exhibits that social support holds a significant association with subjective well-being, meaning that high social support leads to better subjective well-being (Goudarz et al, 2015;Tian, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the result of the study stating that social support and acceptance significantly affect student's subjective well-being (Tian et al, 2015). A study found that social support positively affects Chinese college students' subjective well-being (Xi, Wang, & Jia, 2017). The result of the study conducted on older adults and old exhibits that social support holds a significant association with subjective well-being, meaning that high social support leads to better subjective well-being (Goudarz et al, 2015;Tian, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Associations have also been found in the past literature between religiosity and selfefficacy (Israel-Cohen et al, 2016;Haag, 2008;Hidayatin, 2013;Xi et al, 2017). The individuals, who see themselves as religious, are found to be more self-efficacious (Abdel-Khalek and Lester, 2017).…”
Section: Moderating Effect Of Religiositymentioning
confidence: 76%
“…Self-efficacy positively predicts an increase in older adults’ positive emotions, such as optimism [ 37 ] and happiness [ 38 ]. Moreover, self-efficacy works as a mediator in the relationship between social support and subjective well-being [ 39 ], and mental health [ 40 ]. Accordingly, older adults with high levels of self-efficacy are more likely to cultivate higher positive emotions when compared to those with low levels of self-efficacy.…”
Section: Self-efficacymentioning
confidence: 99%